El clima organizacional y su influencia en la atención al cliente en la plataforma de atención de la Oficina de Normalización Previsional La Libertad. - Calderón Lázaro, Leila Alejandra (2014)
The present study is named “The Organizational Climate and its influence on the Customer Service Platform of Oficina Normalización Previsional La Libertad”, it was intended to deepen two aspects that should concern every institution: the personal welfare of its human resources and its impact on the quality of services it offers, especially those providing services to the public. The main objective of this study was to determine the relationship between organizational climate and its influence on the customer in the Platform for Public Attention ONP La Libertad. The problem that arose for this study is: How organizational climate influences the Customer, the Platform for Public Attention of Oficina Normalización Previsional La Libertad?. To solve this question, the following assumptions were considered: The organizational climate directly influences the Customer, the Platform for Public Attention of Oficina Normalización Previsional La Libertad. In this research two types of population to a to analyze the organizational climate and the other to analyze the Customer was taken. The sample considered for the first population is 12 workers and the second is 60 clients. Also, the technique used to collect data were the Organizational Climate Scale (EDCO) and Customer Satisfaction Survey. the results showed that the Platform care Normalization Office Freedom level organizational climate that prevails is high with 58.33%. And referring to the process of care in the window, determined relative to the speed of answering inquiries, that to the 46% of the speed of guiding clients to absolve inquiry was fair. Therefore it is concluded that organizational climate has a direct influence on the customer's attention on the platform for Public Attention Oficina Normalización Previsional La Libertad. The results of the sample is taken as the value of the correlation coefficient 0.91, which shows that the relationship between the studied variables is positive and significant, showing a positive and significant relationship for both variables.